2015
DOI: 10.1098/rsos.150017
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen deposition and multi-dimensional plant diversity at the landscape scale

Abstract: Estimating effects of nitrogen (N) deposition is essential for understanding human impacts on biodiversity. However, studies relating atmospheric N deposition to plant diversity are usually restricted to small plots of high conservation value. Here, we used data on 381 randomly selected 1 km2 plots covering most habitat types of Central Europe and an elevational range of 2900 m. We found that high atmospheric N deposition was associated with low values of six measures of plant diversity. The weakest negative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…Contrasts between watersheds, as depicted in Table 1, suggest both the profound effect of excess N on herb diversity and the principle mechanism for such an effect. As already reported for this site [24], and consistent with findings of numerous other studies [41][42][43], chronic additions of N to WS3 have significantly (p < 0.05) decreased herb layer diversity. Although both richness and evenness contribute to species diversity, these results reveal that the N-mediated loss of diversity arose from decreased species evenness, which also declined significantly (p < 0.005), and not species richness, which showed no change (Table 1).…”
Section: Change In Herb Diversity Metrics Over Timesupporting
confidence: 92%
“…Contrasts between watersheds, as depicted in Table 1, suggest both the profound effect of excess N on herb diversity and the principle mechanism for such an effect. As already reported for this site [24], and consistent with findings of numerous other studies [41][42][43], chronic additions of N to WS3 have significantly (p < 0.05) decreased herb layer diversity. Although both richness and evenness contribute to species diversity, these results reveal that the N-mediated loss of diversity arose from decreased species evenness, which also declined significantly (p < 0.005), and not species richness, which showed no change (Table 1).…”
Section: Change In Herb Diversity Metrics Over Timesupporting
confidence: 92%
“…A study of soil microbial communities within the experimental plots sampled in the current study found that nutrient addition had distinct effects on different phylogenetic groups of species (Leff et al, ), and our current results suggest that this effect on endophytic fungi might depend on local site. This stands in contrast to the effects of nutrients on the host plant community diversity: elevated nutrient supply can cause local plant species extinctions (Borer, Seabloom, Mitchell, & Cronin, ; Harpole et al, ) as well as reduction in plant phylogenetic diversity (Roth, Kohli, Rihm, Amrhein, & Achermann, ).…”
Section: Discussionmentioning
confidence: 98%
“…In spite of the diverse nature of these six measures, however, low values of plant diversity were consistently associated with high atmospheric N deposition (Roth et al 2015). The current study underpins that N deposition has similar effects on the different aspects of plant diversity.…”
Section: Discussionmentioning
confidence: 99%